Risk Factors for Extended Duration and Timing of Peak Severity of Hot Flashes. - Rebecca Lee Smith; Lisa Gallicchio; Susan R Miller; Howard A Zacur; Jodi A Flaws (PLoS ONE, 2016)
OBJECTIVE:To identify risk factors associated with the duration of hot flashes and the time of peak hot flash severity in mid-life women. METHODS:A cohort of 647 women reporting hot flashes were followed for 1-7 years, with survey data and hormone measurements. Survival analysis determined the association of risk factors with the duration of hot flashes. Linear regression determined the association of risk factors with the time of peak severity. Final models were determined through stepwise model selection. RESULTS:Average hot flash duration was 2.5 years (range: 1-33), with peak severity on average at 2.96 years (range: 1-20). Duration of hot flashes was associated with race, education, menopause status, smoking history, BMI, alcohol consumption, leisure activity levels, and levels of estradiol and progesterone. In the final model, only race, alcohol consumption, leisure activity, and menopause were retained. White women had significantly shorter hot flash durations than non-white women. Women consuming at least 12 alcoholic drinks in the previous year had a significantly shorter duration of hot flashes with a smaller effect of hot flash duration on increasing in time to peak severity compared to those who consumed less than 12 alcoholic drinks in that year. Higher serum progesterone levels were associated with later peak severity if the duration of the hot flashes was less than 2 years and an earlier peak severity otherwise. CONCLUSIONS:These results suggest that some behaviors (such as moderate alcohol consumption) are associated with shorter durations of hot flashes, and that progesterone was associated with the dynamics of hot flash severity.